Roscoe Robinson papers - Robinson, Roscoe, 1928-1993.
Correspondence, cables, speeches, interviews, reports, briefings, notes and notebooks, subject files, chronological files, office files, scrapbooks, newspapers and newspaper clippings, photographs, and other papers pertaining to Robinson's career in the U.S. Army. Documents his service in various positions with the 82nd Airborne Division (1959-1979), in the Vietnamese conflict (1967-1968), as commander of U.S. troops stationed in Japan (1973-1976 and 1980-1982) and in Europe (1978-1980), and as U.S. representative to the North Atlantic Treaty Organization (1982-1985). Includes material relating to African Americans in the armed forces and to Robinson's education at the National War College, Washington, D.C., United States Military Academy, West Point, N.Y., and the University of Pittsburgh's Graduate School of Public and International Affairs, Pittsburgh, Pa.
Correspondents include David M. Abshire, Julius W. Becton, George S. Blanchard, Emmet W. Bowers, Robert F. Cocklin, E. F. Corcoran, William H. Danforth, Jeremiah A. Denton, James M. Gavin, James F. Hamlet, Laurence J. Legere, Ernest A. Nagy, Matthew B. Ridgeway, J. R. Thurman, John W. Vessey, and Alexander M. Weyand.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Paratrooper and first African-American four star general; Roscoe Robinson, Jr.
Collection material in English, French, German, Japanese, and Vietnamese.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abshire, David M. -- Correspondence; Becton, Julius W. -- 1926- -- Correspondence; Blanchard, George S. -- 1920-2006 -- Correspondence; Bowers, Emmet W. -- Correspondence; Cocklin, Robert F. -- Correspondence; Corcoran, E. F. -- Correspondence; Danforth, William H. -- Correspondence; Denton, Jeremiah A. -- Correspondence; Gavin, James M. -- 1907-1990 -- Correspondence; Hamlet, James F. -- Correspondence; Legere, Laurence J. -- Correspondence; Nagy, Ernest A. -- Correspondence; Ridgeway, Matthew B. -- Correspondence; Thurman, J. R. -- Correspondence; Vessey, John William, -- 1922- -- Correspondence; Weyand, Alexander M. -- 1928- -- Correspondence; United States. -- Army -- Foreign service -- Europe; United States. -- Army -- Foreign service -- Japan; United States. -- Army. -- Airborne Division, 82nd.; National War College (U.S.); North Atlantic Treaty Organization; United States Military Academy; University of Pittsburgh. -- Graduate School of Public and International Affairs; African-American soldiers; Universities and colleges -- New York -- West Point; Universities and colleges -- Pennsylvania -- Pittsburgh; Universities and colleges -- Washington (D.C.); Vietnam War, 1961-1975.; United States -- Armed Forces -- African Americans; Army officers; Paratroopers